KEWENANGAN PEJABAT PENGAWAS LINGKUNGAN HIDUPDALAM PENEGAKAN HUKUM LINGKUNGAN DI BIDANG PERTAMBANGAN - Arisandi Mursalin (Badamai Law Journal, 2016)
Environmental quality has been threaten the survival decreased humans and other living things, as well as increasing global warming resulting in climate change and this will exacerbate environmental degradation. It is necessary for the protection and environmental management seriously and consistently by all stakeholders. Preventive measures in order to control environmental impacts need to be implemented by utilizing the most of supervision instruments. In carrying out supervision and monitoring of environmental quality in the area, the Government of Indonesia has a Regional Environmental Officer Supervisor (PPLHD). The formulation of the problem in this thesis is how the role PPLHD, the extent of the responsibilities and constraints faced PPLHD in Environmental Protection and Management in North Sumatra. In doing his research, the authors use a method that describes the normative legal principles in environmental monitoring in region conducted by the Regional Environmental Officer Supervisor. From this research can be concluded that the role PPLH/PPLHD still can not be said to run optimally and in principle, very big responsibility PPLH/PPLHD, besides that there are still many constraints faced by the Regional Environmental Supervision Officer in carrying out tasks tasks and functions. The authors suggested that the role should PPLH/PPLHD maximally activated following the laws and regulations applicable environmental by putting his position in a proportional system of local bureaucracy and the constraints that exist must be addressed both internally and externally